Liquid‐Phase Exfoliated Metallic Antimony Nanosheets toward High Volumetric Sodium Storage. Issue 17 (11th May 2017) - Gu, Jianan; Du, Zhiguo; Zhang, Chao; Ma, Jingui; Li, Bin; Yang, Shubin
Abstract : Metallic antimony (Sb) with gray allotrope has rarely been considered from the viewpoint of two‐dimension layered system is actually a graphite‐like material, in which Sb layers consist of fused, ruffled, and six‐membered rings. Given that metallic Sb nanosheets can be played like graphene, it would be anticipated to obtain a new anode material with superior electrochemical performances for sodium storage. In this work, we propose an efficient strategy to fabricate free‐standing metallic Sb nanosheets via liquid‐phase exfoliation of gray Sb powder in an ios‐propyle alcohol (IPA) solution with a constant concentration of sodium hydroxide. As a proof of the concept, several hybrid films composed of metallic Sb nanosheets and graphene with tunable densities are achieved, in which the notorious volume change of metallic Sb can be efficiently alleviated with the aid of the good flexible graphene, and the whole density of electrode films can be significantly improved by harnessing the high density of Sb nanosheets. As a consequence, the optimized metallic Sb nanosheets‐graphene (SbNS‐G) film displays a high volumetric capacity of 1226 mAh cm –3, high‐rate capability and good cycle performance for sodium storage. Abstract : Metallic antimony nanosheets are fabricated via a facile liquid‐phase exfoliation. The ultrathin nanosheets enable them as building blocks to construct uniform and compacted films with graphene. In these hybrid films, the volume change of metallic antimony can be alleviated via the good flexibility of graphene, leading to novel anode materials with high volumetric capacity, and good cyclic performance for sodium storage.